2023
DOI: 10.54392/bsr2316
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Tamanu Seedlings (Calophyllum inophyllum L.) in flooding on Several Types of Soil

Abstract: Tamanau (Calophyllum inophyllum L.), has economic value as a source of biofuel and medicine, therefore it has the potential to be developed in several wetlands in Riau, Indonesia. This study aims to examine the growth ability and morphological adaptation of tamanu to flooding conditions on mineral soil, peat soil and sand soil. This experimental research was designed using a randomized block design. The experiment consisted of flooded and non-flooded treatments on mineral soils, peat soils and sandy soils. Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Leksono et al [33] compared the survival rates and growth of 2-year-old tamanu on ombrogenous peatland (i.e., higher than surrounding landscapes and receiving water only from precipitation) and topogenous peatland (i.e., directly above the mineral soil and affected by tidal or river runoff) in Central Kalimantan and found that the initial survival rates (more than 80%) and tree growth were promising on both types of peatland. Recently, Fatonah et al [34] showed that tamanu seedlings in peat soil died after 2 cm of flooding for 30 days. However, neither study distinguished the effects of several groundwater levels on the initial growth of tamanu seedlings in peat soil.…”
Section: Introductionmentioning
confidence: 99%
“…Leksono et al [33] compared the survival rates and growth of 2-year-old tamanu on ombrogenous peatland (i.e., higher than surrounding landscapes and receiving water only from precipitation) and topogenous peatland (i.e., directly above the mineral soil and affected by tidal or river runoff) in Central Kalimantan and found that the initial survival rates (more than 80%) and tree growth were promising on both types of peatland. Recently, Fatonah et al [34] showed that tamanu seedlings in peat soil died after 2 cm of flooding for 30 days. However, neither study distinguished the effects of several groundwater levels on the initial growth of tamanu seedlings in peat soil.…”
Section: Introductionmentioning
confidence: 99%